Sialadenoma papilliferum of the hard palate: A rare case report - Saede Atarbashi-Moghadam; Ali Lotfi; Mohammad Moshref; Sepideh Mokhtari (Wolters Kluwer Medknow Publications, 2019)
Sialadenoma papilliferum (SP) is a rare benign salivary gland tumor with unclear cell origin. This report presents a new case of SP of the hard palate occurring in a 50-year-old female. The lesion was completely excised, and the microscopic features were consistent with SP. The knowledge of this rare entity contributes to proper diagnosis and prevents unnecessary radical surgery and treatment.